International Cooperation on Innovation: Empirical Evidence for German and Portuguese Firms - Pedro Faria; Tobias Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
In this paper we investigate the factors that lead firms to cooperate with partners from foreign countries on innovation activities. Portuguese and German data from the harmonised Community Innovation Survey (CIS III) allow us to compare innovation cooperation behaviour of private firms in the two countries. Using a bivariate probit model, we show that the characteristics of firms cooperating with foreigners in both countries are quite similar. International activities other than cooperation, firm size and the importance of protection methods for knowledge have a positive influence in both countries on the decision to cooperate with foreign partners. Some differences remain, however: In Germany, exporters are more likely to cooperate with foreign partners than non-exporters, whereas in Portugal this is not the case.
Keywords: 330; International cooperation; Innovation; CIS III; Germany; Portugal; Innovation; Internationale Unternehmenskooperation; Forschungskooperation; Deutschland; Portugal